GEOMAGNETIC ACTIVITY AND EFFECTIVENESS OF MILLIMETER ELECTROMAGNETIC RADIATION IN UNSTABLE ANGINA TREATMENT - Parshina, S. S.; Samsonov, S. N.; Afanas’yeva, T. N.; Tokayeva, L. K.; Petrova, V. D.; Dolgova, E. M.; Manykina, V. I.; Vodolagina, E. S. (Одеські астрономічні публікації, 2014)
There had been performed a research of an effectiveness of millimeter electromagnetic radiation (MM EMR) use in patients with an unstable angina (UA) at periods of a lower (daily value of Kp-index 16,19±0,18) and a higher (daily value of Kp-index 17,25±0,21, p<0,05) gemagnetic activity (GA). It was found that involving of the MM EMR (the wave length7.1 mm) into the treatment of the patients with an UA, enhances an antianginal effect of a drug therapy independently on the period of GA. The MM EMR at the period of a lower geomagnetic activity (LGA) enhances the decrease of diastolic blood pressure (BP), and at the period of a higher geomagnetic activity (HGA) – the decrease of systolic BP. At a HGA there were noted: a quick and more serious antianginal effect, maximal antihypertensive effect was achieved quicker, but (as opposed to the period of a LGA) there was no a pulse slowing effect of a MM EMR. Including the MM EMR into the treatment accelerates stabilization of the patients’ condition only at a LGA. Positive effect on blood rheological properties is an independent effect of MM EMR, and it is in blood viscosity reduce in microcirculatory at both of the periods of GA. Normalization of blood viscosity under the MM EMR is only at the period of a LGA. So, the effect of MM EMR on a clinical condition of the patients is more evident at the period of a HGA, blood viscosity – at the period of a LGA.